Analysis on the behaviour of the transient response in turbocharger diesel engine by using simulation / Ahmad Nasrullah Norazaman - Ahmad Nasrullah, Norazaman (2012)
The turbocharger is a centrifugal compressor powered by a turbine that is driven by an engine's exhaust gases. The engine performance in a turbocharged depends on engine speed, turbocharger speed, air fuel ratio, air flow rate, boost pressure, fuel pump rack position, exhaust temperature, initial applied load, combustion efficiency and so on. The objective of this project is to study the engine performance under transient response in a turbocharged diesel engine. The effect of the transient response on turbocharger diesel engine by simulation using Fortran language. The estimated accuracy of the simulation The variable control are the initial applied load from 2, 4, 6, and 8 bar, the engine speed from instrumentation is ±5%. 500, 1000, 1500 and 2000 rpm and the dynamometer delay time from 500, 1000, 1500 and 2000 ms. The result by a simulation shown in Chapter 4 from Figure 4.1 until 4.10. So for the conclusion this programmed can be use to get predict the engine performance in a turbocharger diesel engine.